PSXVI-28 Late-Breaking: Effects of Preconditioning (Value Added Programs) on the Health, Performance, Mannheimia haemolytica, and Pasteurella multocida in Cattle Received on Winter Wheat Pasture. (8th October 2021) - Brooks, Josiah M; Randall, Jennifer; Steiner, Robert; Briggs, Robert; Duff, Glenn C
Abstract: Bovine respiratory disease (BRD) is a persistent health problem impacting the beef industry. Research shows improved health and performance in preconditioned (PRECON) calves compared with nonpreconditioned (NONPRE) or commingled (COMM) calves received in the feedlot but little research has been focused on calves received on winter wheat pasture prior to feedlot entry. Our objective for this presentation is to investigate the effects of preconditioning on the health and performance of newly received beef calves on winter wheat pasture. Mixed breed steers (n = 145) were purchased from an auction barn in Dalhart, Texas, as PRECON (n = 70) or NONPRE (n = 75) and were transported to the Clayton Livestock Research Center in Clayton, New Mexico, for this 112-d study trial. Three treatments were used in this completely randomized design: PRECON (n = 50), NONPRE (n = 50) and COMM (n = 45). Upon arrival, steers were offloaded into separate pens. On d 0, steers were processed using a standard health protocol along with collection of nasopharyngeal (NP) swabs, randomly allocated to treatment, and released onto a 120-acre winter wheat pasture split into three paddocks with a common water source; weights were collected again on d 2, 90, and 112. There were no statistical differences in morbidity and mortality rates between treatments. Weight gain was analyzed using PROC GLM of SAS from d 0 to d 90. COMM steers had greater weight gains than PRECON (P = 0.04) and NONPRE (P = 0.02) steers. NP swabs were used to show the distribution of Mannheimia haemolytica (MH) serotype A1, A2, and A6 and Pasteurella multocida (PM) by day and by treatment. No statistical differences were observed in serotype distribution of MH A1, A2, or A6 or in PM. PRECON steers displayed no health or performance advantage over NONPRE or COMM steers.